2022
DOI: 10.1111/sltb.12840
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Hunter Way Back Support Service: An historical controlled trial of a brief non‐clinical after‐care program for hospital‐treated deliberate self‐poisoning

Abstract: Introduction Active contact and follow‐up interventions have been shown to be effective in reducing repetition of hospital‐treated self‐harm. The Way Back Support Service (WBSS) is a new service funded by the Australian government to provide three months of non‐clinical after‐care following a hospital‐treated suicide attempt. The aim of this study was to investigate the effectiveness of WBSS in reducing deliberate self‐poisoning (DSP) and psychiatric hospital admissions over a 12‐month follow‐up period for a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…A historical controlled study found that no significant differences were observed between the Way Back intervention and the control group in terms of the proportion of individuals with any readmissions for suicide re-attempts or the number of readmissions during the follow-up period. 18 Further research on the implementation, acceptability, feasibility and sustainability of brief aftercare interventions is therefore needed so that local, more specific estimates of their short-term and long-term effectiveness can be generated. Furthermore, research to explore which of various different aftercare models are the most effective and cost-effective for suicide prevention should be carried out to support the best funding allocation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A historical controlled study found that no significant differences were observed between the Way Back intervention and the control group in terms of the proportion of individuals with any readmissions for suicide re-attempts or the number of readmissions during the follow-up period. 18 Further research on the implementation, acceptability, feasibility and sustainability of brief aftercare interventions is therefore needed so that local, more specific estimates of their short-term and long-term effectiveness can be generated. Furthermore, research to explore which of various different aftercare models are the most effective and cost-effective for suicide prevention should be carried out to support the best funding allocation.…”
Section: Discussionmentioning
confidence: 99%
“…17 The effectiveness of a theoretical brief aftercare intervention was based on an effect size derived from a recent meta-analysis by Doupnik et al, 13 whereas the direct intervention cost was based on estimates from the Australian brief aftercare programme for prevention of repeated self-harm. 18 In this study, a partial societal perspective was used to assess both the costs and health benefits. That meant that healthcare costs related to hospital admissions due to self-harm and the healthcare cost offsets and cost of productivity loss related to suicides were included in the base case analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPP includes a number of suicide specific interventions, such as safety planning, counselling on access to lethal means, consumer and carer psycho-education, and face-to-face contact with a mental health clinician within 48 h of discharge [ 8 ]. One aim was rapid connection of those who do not require ongoing public mental health support to other community support services, including primary care, private sector and non-clinical aftercare services, such as The Way Back Support Service (a not-for-profit organization providing non-clinical psychosocial support and transition services for individuals who have attempted or are at risk of suicide) [ 9 ]. High quality clinical handover in this transition phase was emphasised.…”
Section: A Case Study: the Gold Coast Suicide Prevention Pathwaymentioning
confidence: 99%
“…Responding to the risk and impact of suicide across the healthcare system requires a careful balance, incorporating diagnosis, risk and clinical care with suicide-specific and non-clinical care interventions. A recent evaluation of The Way Back Support Service (providing non-clinical aftercare after hospital treated suicide attempts) illustrates this by showing that non-clinical aftercare by itself had limited impact on those presenting with deliberate self-poisoning, indicating the need for evidence-based clinical interventions alongside the non-clinical care [ 9 ].…”
Section: Introductionmentioning
confidence: 99%